Hypercoagulable state among thalassemia major patients - Hassan, Wan Amal Hayati Wan (2013)
Increased incidence of thromboembolism among thalassemia patients had triggered various studies to determine hypercoagulable state among thalassemia patients. Several factors for the hypercoagulable state had been identified such as red blood cell membrane disruption, chronic platelet activation and defect in coagulation pathway. The objectives of this study were to determine the level of Protein C, Protein S and Antithrombin III among thalassemia major patients and to compare the level of these natural anticoagulants between thalassemia major patients and healthy controls. For this purpose, a case control study was conducted in Hospital Universiti Sains Malaysia (HUSM). Thirty six thalassemia patients who came for regular blood transfusion and twenty healthy blood donors for normal control were recruited. Blood samples were collected and analysed for Protein C, Protein S, Free Protein S and Antithrombin III using ACL Elite Pro coagulometer. The results showed mean Protein C, Protein S and Free Protein S levels were significantly lower in thalassemia patients (54.54 ± 13.22,94.41 ± 18.73 and 70.09 ± 12.32 ; respectively ) compared to normal controls (94.14 ± 16.34 , 105.12 ± 16.79 and 99.79 ± 17.33 ; respectively) Mean Antithrombin III showed no significant difference compared to normal controls (116.09 ± 27.28 and 124.36 ± 12.49 respectively). There were no significant differences of mean Protein C, Protein S, Free Protein S and Antithrombin III between splenectomised and non splenectomised patients. No thromboembolic events were documented in this study. In conclusion, significantly decreased Protein C and Protein S in thalassemia patients suggest hypercoagulable state in those patients. However further studies need to be done to look for other parameters contributing to hypercoagulable state in thalassemia patients. A normal antithrombin level could be due to protective effect of regular transfusion, a further study need to be done to prove this hypothesis. Besides, thromboembolic event can be subclinical, therefore a further study is needed to follow up the patients and to detect subclinical thrombosis.